Fighting Body Ideal Construction in America as Expressed in Julie Murphy’s Dumplin’ - Resty Maudina Septiani (English Department, Faculty of Humanities, Andalas University, 2021)
Not only marginalize and discriminate big-size women, social contruction of ideal body has contribute to eating disorder and anorexia on women in America. Thus it triggers rejections of protest through all platforms and one of them is Julie Murphy’s Dumplin’. The purpose of this research is to reveal Julie Murphy’s worldview of fighting discrimination because of social construction in novel Dumplin’. Dumplin’ is chosen as the material object of this study. The formal object of this study is how the main character fight the social construction through its relation with other characters. Julie Murphy’s Dumplin’ is believed to express the social group world vision thus Lucien Goldmann genetic structuralism theory is used. Dialectical method is used to achieve the purpose of this study. The primary data are taken from Dumplin’ novel. The secondary data are taken from journals and books related to this study. The focus of the research are 1) analyzing the literary structure of the novel through the relations of its characters, 2) finding the genesis of the novel by analyzing the social structure, 3) the author’s (social group) worldvision in the novel. Therefore, the structure of the novel are analyzed through the characters relations and the genesis found as the social structure investigated and analyzed. The result of analysis shows that the author World View represents social groups fighting againsts body ideal construction such as NAAFA, The Fat Acceptance Movement and Body Positivity Movement that try to fight and modify the body ideal construction as dominant social construction that exists in society through her novel Dumplin’.